2020
DOI: 10.1097/md.0000000000023392
|View full text |Cite
|
Sign up to set email alerts
|

Association of glycosylated hemoglobin and outcomes in patients with COVID-19 and pre-existing type 2 diabetes

Abstract: Background: The impact of glycosylated hemoglobin on mortality in patients with coronavirus disease 2019 (COVID-19) and type 2 diabetes (T2D) remains uncertain. In this study, we aim to assess the effect of pre-hospital blood glucose regulation on patients with COVID-19 and pre-existing T2D. Methods: All randomized controlled trials (RCTs) and cohort studies of association of glycosylated hemoglobin and outcomes in patients with COVID-19 and T2D will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A large body of evidence indicates that statins improve cardiovascular outcomes through lipid-lowering and non-lipidlowering effects [59,60]. Prior studies have also shown improved outcomes in patients taking indicated drug therapy for hypertension [61] and diabetes mellitus [62]. Hence, the observed reduced mortality with statins in COVID-19 could be explained at least in part through their favorable effects on the cardiovascular system.…”
Section: Mechanismsmentioning
confidence: 99%
“…A large body of evidence indicates that statins improve cardiovascular outcomes through lipid-lowering and non-lipidlowering effects [59,60]. Prior studies have also shown improved outcomes in patients taking indicated drug therapy for hypertension [61] and diabetes mellitus [62]. Hence, the observed reduced mortality with statins in COVID-19 could be explained at least in part through their favorable effects on the cardiovascular system.…”
Section: Mechanismsmentioning
confidence: 99%
“…A prior study indicated that glycemic control correlated with outcomes in COVID. 37 It would follow that diabetic medications act both as a marker of illness and a marker for higher likelihood of controlled illness. Thus, diabetes medications may correlate with both positive and negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies show hyperglycemia, caused by inadequate glycemic control, has been identified as a risk of COVID-19 development and poor survival [28] . In one large study carried out on 7000 individuals with nCOVID-19 in Wuhan, China, among a group with nCOVID-19 and T2DM, patients with good glycemic control reported a significant decrease in overall comorbidities and all-cause mortalities compared to those with poor glycemic control [29] . In other research, increased levels of blood glucose levels at the initial assessment were linked to more hospitalization, more in-hospital morbidity, and mortality [30] .…”
Section: Mechanisms Linking Obesity To Ncovid-19mentioning
confidence: 99%